2021
DOI: 10.11606/issn.1678-4456.bjvras.2021.168702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cryoprotectant on the motility, viability, fertilization, and DNA integrity of naleh fish Barbonymus sp. (Cyprinidae) sperm

Abstract: Naleh fish Barbonymus sp. is a commercial freshwater fish, which is indigenous to Aceh, Indonesia. The population of this species has declined over the years as a result of habitat perturbations and overfishing. Hence, the crucial need to develop a cryopreservation method to support breeding programs. This involved the use of a cryoprotectant as an important component. The objective of this study, therefore, was to explore the best cryoprotectant for naleh fish spermatozoa, and a total of five types were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…Egg yolk protein and lecithin function to protect sperm from damage caused by temperature shock by maintaining the integrity of lipoproteins in the plasma membrane of spermatozoa (Zambrowicz et al, 2014;Sunwoo and Gujral 2015). Therefore, the use of intracellular and extracellular cryoprotectants provides optimal protection as recorded in this study, the similar finding was also reported by several researchers (Muthmainnah et al, 2018;Muchlisin et al, 2020;Maulida et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Egg yolk protein and lecithin function to protect sperm from damage caused by temperature shock by maintaining the integrity of lipoproteins in the plasma membrane of spermatozoa (Zambrowicz et al, 2014;Sunwoo and Gujral 2015). Therefore, the use of intracellular and extracellular cryoprotectants provides optimal protection as recorded in this study, the similar finding was also reported by several researchers (Muthmainnah et al, 2018;Muchlisin et al, 2020;Maulida et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The effectiveness of DMSO as a cryoprotectant has been reported in several studies. Maulida et al (2021) reported that it was effective for preserving naleh fish Barbonymus sp. sperm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several fish species have shown a slightly acidic semen pH, such as common carp Cyprinus carpio L. (Pradana et al, 2020) and Barbonymus sp. (Maulida et al, 2021). Some other fish species have alkaline sperm, such as Schizothorax progastus (Agarwal et al, 2013), Schizothorax richardsonii (Raghuvanshi et al, 2019) and Labeo rohita (Bibi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, significant progress has been made in the process of cryopreservation of fish sperm, and, as a result, fertilization. Progress was associated with the use of new cryopreservation methods, including the search for new tread compositions [7][8] and high-speed freezing modes [9], which lead to better cryo-survival of spermatozoa.…”
Section: Introductionmentioning
confidence: 99%